ANALISIS PENGELOLAAN BARANG INVENTARIS PADA BIRO UMUM SEKRETARIAT DAERAH PROVINSI SULAWESI SELATAN - Benget Hutagaol (KAIZEN : Kajian Ekonomi, Manajemen, Akuntansi, dan Kewirausahaan, 2026)
This study aims to examine the sub-systems that affect inventory management at the General Bureau of the Regional Secretariat of South Sulawesi Province. The research method used is a survey by describing the management of inventory at the General Bureau of the Regional Secretariat of South Sulawesi Province. The sample used is Stratified Random Sampling, using questionnaires as the main tool for data collection. The research results were tabulated into frequency tables. The results show that inventory management has not been able to contribute to improving effective inventory management because the procurement planning pays little attention to the quality of goods, procurement planning is not adjusted to the needs of work units, there is no adjustment of procurement implementation to the prevailing regulations, and the distribution of goods is still relatively uneven across work units.